The correlation analysis of dental caries, general health conditions and daily performance in children aged 2-5 years old - Darmawan Setijanto; Taufan Bramantoro; Nanissa Dyah Anggraini; Ardhyana Dea Maharani; Dwita Angesti; Dani Susanto Hidayat; Aulia Ramadhani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Oral health is important for general health and quality of life. One of the oral diseases with a high prevalence in Indonesia is dental caries. Dental caries can cause limiting disturbances of daily activities such as biting, chewing, smiling and talking, and of psychosocial well-being, including development and general health of children. Purpose: This study aims to analyse the correlation of dental caries incidence rate with general health conditions and daily performance of children aged 2–5 years. Methods: This was an analytical observational cross-sectional study. The study sample was 103 pairs of children and their mothers, selected using cluster random sampling technique. Intra-oral examination was conducted on the children to obtain decay, missing, filled-teeth (DMF-T) index score. Information about oral impacts on daily performance (OIDP) of the children was collected through a questionnaire distributed to the mothers. The data obtained were statistically analysed with a regression test (p < 0.05). Results: It was found that dental caries had a significant correlation with general health (p = 0.00) and daily performance, including chewing function disorder (p = 0.00), difficulties in maintaining oral health (p = 0.039), sleep disorders (p = 0.00), and emotional instability (p = 0.00). Conclusion: The incidence rate of dental caries has a significant effect on the general health conditions and daily performance of children aged 2–5 years.